The Influence of Covid-19 on Publications in Economics: Bibliometric Evidence from Five Working Paper Series - Constantin Bürgi; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2022)
We compare Covid-related working papers in economics to non-Covid-related working papers in four dimensions. Based on five well-known working papers series and data from the RePEc website, we find that Covid papers are mainly cover topics in macroeconomics and health, they are written by larger teams than non-Covid papers, are more often downloaded and they receive more citations relative to non-Covid papers.
Keywords: A10; A12; I00; 330; Covid; Corona; pandemic; citations